Research prevalence of psoriasis in countries and Ukraine - А. А. Kotvitska; V. V. Carlo (Zaporožskij Medicinskij Žurnal)
Introduction. In recent years there was a negative trend growth of dermatological diseases. One of the first places in the practice of dermatology has psoriasis, which today, unfortunately, is not a “disease” but lifelong condition.